Figural reading and the Old Testament : theology and practice - Collett, Don C., 1963- (Grand Rapids, Michigan : Baker Academic, 2020)
"Examines the tension between figural and literal modes of exegesis and offers theological readings of several significant Old Testament passages"--
Introduction: A world well lost : The eclipse of Old Testament consciousness -- Biblical models for figural reading -- Figural reading and scripture's literal sense -- Figural reading, metaphor, and theological exegesis -- Figural reading and modernity.
Includes bibliographical references (pages 167-180) and indexes.
Keywords: Bible. -- Hermeneutics; Bible. -- Criticism, interpretation, etc